Epithelial expression and role of secreted STC1 on asthma airway hyperresponsiveness through calcium channel modulation - Xu, Jiayan; Meng, Yaqi; Jia, Man; Jiang, Jie; Yang, Yi; Ou, Yingwei; Wu, Yunhui; Yan, Xiaoyi; Huang, Mao; Adcock, Ian M.; Yao, Xin (Allergy (Copenhagen), 2021)
Background Asthma is characterized by airway hyperresponsiveness (AHR), inflammation, and airway remodeling. Airway hyperresponsiveness results from enhanced airway smooth muscle (ASM) contraction potentially under the control of an epithelium‐derived relaxing factor (EpDRF). However, relatively rare is known about EpDRF. We aimed to elucidate the role of epithelium‐derived stanniocalcin‐1 (STC1) on AHR and ASM contraction. Methods Stanniocalcin‐1 levels in the serum of asthmatic patients and healthy volunteers and in bronchoalveolar lavage fluid (BALF) from ovalbumin (OVA)‐challenged mice were measured by ELISA. The effects of exogenous STC1 on AHR and on inflammation were examined in mice. IL‐13 modulation of STC1 mRNA and protein levels was studied in human bronchial epithelial cell lines (16HBE). The function of STC1 on Ca2+ influx and ASM contraction was examined ex vivo. Results Serum STC1 was decreased in asthma (n = 93) compared with healthy volunteers (1071 ± 30.4 vs 1414 ± 75.1 pg/ml, p < 0.0001, n = 23) and correlated with asthma control (p = 0.0270), lung function (FEV1, p = 0.0130), and serum IL‐13 levels (p = 0.0009). Treatment of ten asthmatic subjects with inhaled corticosteroids/long‐acting beta2‐agonists (ICS/LABA) for 1 year enhanced STC1 expression which correlated with improved asthma control (p = 0.022). STC1 was mainly expressed in bronchial epithelium and intranasal administration of recombinant human STC1 (rhSTC1) reduced AHR and inflammation in mice. IL‐13 suppressed STC1 release from 16HBE, whereas rhSTC1 blocked store‐operated Ca2+ entry (SOCE) by suppressing stromal interaction molecule 1 (STIM1) and further inhibited ASM cell contractility by suppressing Ca2+‐dependent myosin light chain (MLC) phosphorylation. Conclusion Our data indicate that STC1 deficiency in asthmatic airways promotes STIM1 hyperactivity, enhanced ASM contraction, and AHR. STC1 may be a candidate EpDRF. Serum levels of STC1 were decreased in asthma and correlated with asthma control and lung function. STC1 was mainly expressed in the bronchial epithelium and intranasal administration of rhSTC1 reduced AHR and inflammation in mice. IL‐13 suppressed STC1 release from 16HBE cells, whereas rhSTC1 blocked SOCE by suppressing STIM1 and further inhibited ASM cell contractility.